The Belt and Road Initiative and Comprehensive Regionalism in Central Asia - Qoraboyev, I.; Moldashev, K. (Palgrave Macmillan, 2018)
This chapter contributes to comparative regionalism studies by exploring the Belt and Road Initiative (BR) as an emerging regionalism project. We start by stating a need for broad conceptual frameworks to study the BR dynamics and consider the “world of regions” framework as such an alternative to mere geopolitical approaches. Subsequently, we evaluate BR as a regional initiative based on China-Central Asia relations. The last section discusses the perspective of the BR in Central Asia by exploring identity issues and regional peculiarities. We argue that the success of the BR in Central Asian depends on its ability to contribute to political independence, provide economic opportunity, and strengthen security in the region.
Keywords: The Belt and Road Initiative, Comprehensive Regionalism in Central Asia, China-Central Asia relations